Benchmarking post-hartree-fock methods to describe the nonlinear optical properties of polymethines: an investigation of the accuracy of algebraic diagrammatic construction (ADC) approaches - Knippenberg, Stefan; Dreuw, Andreas (Journal of chemical theory and computation, 2016)
Third-order nonlinear optical (NLO) properties of polymethine dyes have been widely studied for applications such as all-optical switching. However, the limited accuracy of the current computational methodologies has prevented a comprehensive understanding of the nature of the lowest excited states and their influence on the molecular optical and NLO properties. Here, attention is paid to the lowest excited-state energies and their energetic ratio, as these characteristics impact the figure-of-merit for all-optical switching.